The Relationship Between The Level Of Self-Efficacy On Medication Adherence In Pulmonary Tuberculosis Patients At Imelda General Hospital Indonesia - Naibaho, Eka Nugraha V.; Nasution, Sastri Meyani; Ritonga , Yuni Shanti (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2024)
Pulmonary tuberculosis, one of the infectious diseases, is ranked fifth as an infectious disease that causes the most deaths in the world. Treatment with a long enough period of time allows non-adherence behavior in taking medication in pulmonary TB patients. Self-efficacy is a person's belief in his ability to achieve a desired goal. The purpose of the study was to determine the relationship between the level of self-efficacy on medication adherence in tuberculosis patients at the Imelda General Hospital of Indonesian Workers in 2023. Quantitative research method with correlational descriptive. The study was conducted at the Imelda Pekerja Indonesia General Hospital in August 2023. Population of 282 Pulmonary TB patients, study sample 73 people with Purposive Sampling. Bivariate test using Chi Square. The age of the majority of pulmonary tuberculosis respondents aged 26-35 years (Early Adulthood) was 25 people (34.2%), the gender of the majority of pulmonary tuberculosis respondents was 40 people (54.8%), the majority of pulmonary tuberculosis respondents were employed as 48 people (65.8%). The level of self-efficacy in pulmonary tuberculosis patients was the majority of high self-efficacy scores >77 as many as 55 people (75.3%), followed by low self-efficacy scores of <63 as many as 10 people (13.7%) and moderate self-efficacy scores of 64-76 as many as 8 people (11.0%). Adherence to taking medication in pulmonary tuberculosis patients the majority had moderate adherence scores 1-2 as many as 42 people (57.5%), followed by high adherence score 0 as many as 21 people (28.8%) and low adherence score >2 as many as 10 people (13.7%). There was no relationship of self-efficacy on medication adherence with a p value of 0.324>0.05.